2000
DOI: 10.1002/1520-6300(200009/10)12:5<633::aid-ajhb8>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical activity on bone mineral density assessed by limb dominance across the lifespan

Abstract: Bone mineral density is higher in dominant vs. nondominant limbs, implying that the greater use of dominant limbs in everyday activities results in the deposition of more bone or that the dominant limb is genetically larger. The objective of the present study was to determine whether bone mineral density differences between dominant and nondominant arms were greater in older vs. younger women. To determine whether this was due to a greater lifetime of preferential loading of the dominant arm, differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…(36) Significant differences in trabecular but not cortical properties were found between left and right limbs at maturity (data not shown). Asymmetry in bone properties has been reported in humans (37)(38)(39)(40)(41)(42)(43)(44) and rodents. (30,45) The use of the contralateral limb as an internal control, which has become common in bone studies, (38,(46)(47)(48)(49)(50)(51) should therefore be used with discretion (e.g., randomize left and right limbs).…”
Section: Figmentioning
confidence: 89%
“…(36) Significant differences in trabecular but not cortical properties were found between left and right limbs at maturity (data not shown). Asymmetry in bone properties has been reported in humans (37)(38)(39)(40)(41)(42)(43)(44) and rodents. (30,45) The use of the contralateral limb as an internal control, which has become common in bone studies, (38,(46)(47)(48)(49)(50)(51) should therefore be used with discretion (e.g., randomize left and right limbs).…”
Section: Figmentioning
confidence: 89%
“…the left hand and left leg, similar to a permanent tendency to turn in a given direction when rotating round the long body axis, may lead to asymmetry manifested in morphological characteristics, which as a consequence may affect the volume of bone mass in competitive athletes (Starosta, 2008). It has been shown that asymmetry is greater in the dominant extremity due to its more frequent use in the majority of activities performed during the day, which in turn leads to greater bone dimensions in this body segment (Chilibeck et al, 2000).…”
Section: Introductionmentioning
confidence: 89%
“…Cross-sectional studies that compare the limbs within the same individual reduce the confounding effect of selection bias. Significant differences in bone density and structure between the dominant and non-dominant limb are attributed to lifetime loading of the favoured dominant side ( 39 , 40 ) . The effect of loading is even more marked when comparing the arms of racquet-sport players.…”
Section: Cross-sectional Unilateral Studiesmentioning
confidence: 99%